2010
DOI: 10.1111/j.1741-4520.2010.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic abnormality of SRY gene in the adult XY female with pericentric inversion of the Y chromosome

Abstract: In normal ontogenetic development, the expression of the sex-determining region of the Y chromosome (SRY) gene, involved in the first step of male sex differentiation, is spatiotemporally regulated in an elaborate fashion. SRY is expressed in germ cells and Sertoli cells in adult testes. However, only few reports have focused on the expressions of SRY and the other sex-determining genes in both the classical organ developing through these genes (gonad) and the peripheral tissue (skin) of adult XY females. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…This inversion did not lead to position-effect variegation, but the streak gonads presented abnormally prolonged SRY expression. Thus, the authors believed that the regulation of the SRY gene was impaired, causing gonadal dysgenesis (13). Different from the previously described patients, in the patient described here, histological study identified a testis without characteristics of a dysgenetic gonad, and no abnormalities in the encoding region of SRY or 5'-UTR were detected.…”
Section: Discussioncontrasting
confidence: 73%
“…This inversion did not lead to position-effect variegation, but the streak gonads presented abnormally prolonged SRY expression. Thus, the authors believed that the regulation of the SRY gene was impaired, causing gonadal dysgenesis (13). Different from the previously described patients, in the patient described here, histological study identified a testis without characteristics of a dysgenetic gonad, and no abnormalities in the encoding region of SRY or 5'-UTR were detected.…”
Section: Discussioncontrasting
confidence: 73%
“…Interestingly, the generation and comparison of XY Jmjd1a -deficient mice, which carried the Y chromosome from either CBA (Y CBA ) or B6 (Y B6 ) on a B6N autosomal background, revealed that the sex-reversal phenotype was dependent on not only the loss of Jmjd1a but also the genetic origin of the Y chromosome combined with the B6 background [ 26 ]. In the case of the XY female in humans, without a functional mutation in SRY , pericentric inversion of the Y chromosome causes XY females: if SRY is inverted and relocated to the center of the heterochromatic region, this positional variegation will lead to SRY gene silencing, inducing XY female development [ 17 , 31 , 32 ]. These facts indicate that, even if Sry is intact, the interaction between Sry and other genes will cause sex reversal because Sry expression is regulated in a strictly temporal and spatial manner.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that alterations of the epigenetic regulatory mechanisms or epigenetic states are responsible for the genesis and/or fixation of certain DSDs. To illustrate, consider the study of Mitsuhashi et al () in which the gonadal tissue and fibroblasts were examined in a 17‐year‐old woman suspected of having DSD by cytogenetic, histological, and molecular analyses. The patient was found to have the 46,X,inv(Y)(p11.2q11.2) karyotype and streak gonads with abnormally prolonged SRY expression.…”
Section: Perspectivesmentioning
confidence: 99%
“…Further, the acetylated histone H3 levels in the SRY region were significantly high relative to those of the normal male. It was concluded that since SRY is epistatic in the sex‐determination pathway, the prolonged SRY expression possibly induced a destabilizing effect on the expressions of the downstream sex‐determining genes, suggesting that correct regulation of SRY expression is crucial for normal male sex differentiation, even if SRY is translated normally (Mitsuhashi et al, ).…”
Section: Perspectivesmentioning
confidence: 99%